Answer:
x = -1, 0, and 4
Step-by-step explanation:
Step 1: Set the expression equal to zero. Solving means to find out what values of x make the equation equal zero.
3x³ - 9x² - 12x = 0
Step 2: Factor out the largest common factor is there is one.
Here the largest common factor is 3x. Now we have
3x(x² - 3x - 4) = 0
Step 3: Factor the quadratic expression x² - 3x - 4
3x(x - 4)(x + 1) = 0 (two numbers that add up to -3 and multiply to -4)
Step 4: Set each term equal to zero and solve..
3x = 0, so x = 0 (divide both sides by 3 to isolate x)
x - 4 = 0, so x = 4 (add 4 to both sides to isolate x)
x + 1 = 0, so x = -1 (subtract 1 from both sides to isolate x)
So our solutions are
x = -1, 0, and 4